Relations Between Verbal Language and Visual Image in Student’s Textbook Implementing the Concept of Metafunctions - Nisak, Sukrun; Rukmini, Dwi (Universitas Negeri Semarang, 2021)
This research is about the use of verbal language and visual image to realize the metafunctions in student’s textbook. In order to see the process of meaning making in multimodal text, the researcher analyses the implementation of ideational, interpersonal, and textual meaning. The data was taken from conversation sections in Interchange Student’s Book 1. It consists of verbal language in the form of dialogues and visual image in the form of pictures. There were 16 conversation sections chosen from 16 chapters in the book. This research uses multimodal discourse analysis; using three instruments to classify the data. The checklists are from Eggins (2004) about metafunctions in verbal language, Van Leeuween (2006) about metafunctions in visual image, and Royce (2007) about the relations in verbal language and visual image. In ideational meaning, the result of the study shows that verbal language which dominates the conversation is the material proces; while in visual image, the reactional process is the highest number of process happens. Thus, the verbal-visual relations in ideational meaning found are collocation and repetition. Furthermore, the result in interpersonal meaning finds out that the most common verbal language used is statement; while in visual image, the medium shot is mostly found. Thus, the verbal-visual relation in interpersonal meaning realized through reinforcement of address is interaction between represented participant and represented participant. Moreover, in textual meaning, the result of verbal language shows that the most common used theme is topical theme; while in visual image, the information value is mostly left-right. Thus, the verbal-visual relation in textual meaning shown in reading path is left-right.